Long Term Evolution -Self Organizing Network for Minimization of Sudden Call Termination in Mobile Radio Access Networks - Duraipandian, M. (Journal of Trends in Computer Science and Smart Technology, 2020)
Nowadays the mobile devices have become a more vital requisite and very crucial portion of our lives daily routine. The sudden call termination that happens unexpectedly (call drops) is a circumstance were the enduring calls get cut without any prior indication. The evolution of the services associated with the 3G and the 4G based on the voice and the data has ended up in high conflicts between the companies of the telecommunication to increase the consumer rate leading to major occurrence of the termination in the calls. Such abrupt un-notified call cessation still remains as an unanswered question in the telecommunication industry all over the world. Manifold measures and the researches put forth to devise the solution to the issue of un-notified call cessation for the mobile radio access networks were not successful as every methodology had its own advantages and as well as disadvantages. The laid out research made efforts to discover the reasons that for this un-notified sudden termination of calls, and examines the problem related with the termination of calls in each phase of the radio technology and puts forth the Self Organizing Network in the LTE for minimizing the factors that are related to the call termination and enhances the quality of the voice calls. Further brings down the expenses on the capital and the operations on terms of structural and the configuration attributes.
Keywords: Long Term Evolution; Self-Organizing Networks; Call Termination; Mobile Radio Access Network; Telecommunication